Photodynamic therapy using talaporfin sodium for non-totally resectable malignant glioma - Shinjiro Fukami; Jiro Akimoto; Kenta Nagai; Yuki Saito; Michihiro Kohno (Photodiagnosis and Photodynamic Therapy)
Background: For malignant glioma, intraoperative photodynamic therapy (PDT) using talaporfin sodium is a powerful tool for local tumor control, when gross total removal is performed. However, the efficacy of PDT for non-totally resectable malignant glioma has not been clearly confirmed. Therefore, the purpose of this study was to clarify the usefulness of PDT using talaporfin sodium for non-totally resectable malignant glioma. Methods: Eighteen patients with malignant glioma (16 new onset, 2 recurrent) in whom gross total removal was judged to be difficult from the images obtained before surgery were evaluated. Fifteen patients had glioblastoma (14 newly diagnosed, 1 recurrent), and 3 patients had anaplastic oligodendroglioma (2 newly diagnosed, 1 recurrent). The whole resection cavity was subjected to PDT during the surgery. For newly diagnosed glioblastoma, postoperative therapy involved the combined use of radiation and temozolomide. Bevacizumab treatment was also started at an early stage after surgery. Results: In some patients, reduction of the residual tumor was observed at an early stage of chemoradiotherapy after the surgery, suggesting the positive effect of PDT. Recurrence occurred in 15 of the 18 patients during the course of treatment. Distant recurrence occurred in 8 of these 15 patients, despite good local tumor control. In the 14 patients with newly diagnosed glioblastoma, the median progression-free survival was almost 10.5 months, and the median overall survival was almost 16.9 months. Conclusions: PDT for malignant glioma is expected to slightly improve local tumor control for non-totally resectable lesions.